HIDUP AKRAB DENGAN AL-QUR'AN; KAJIAN LIVING QUR'AN DAN LIVING HADIS PADA MASYARAKAT INDRAGIRI HILIR RIAU - Ridhoul Wahidi (Universitas Islam Negeri Imam Bonjol Padang, 2013)
Living the Quran and Hadith is a relatively new study has not been touched. In addition, this study alsoprovides a new paradigm for the development of the study of the Qur'an and Hadith contemporary era thatno longer dwell on the study of texts alone. The results of this study indicate that the living Quran starts fromthe phenomena of life in the middle of the Muslim community associated with the Koran as an object ofstudy so that the entrance area of social studies, this phenomenon appears by the presence of the Koran, theninitiated into study of the Koran. Similarly, what happened in the Living Tradition. Living Tradition is aform of understanding traditions that are in the field praxis levels. Therefore, what is executed in the mostunequal society in accordance with the mission of the Prophet, but differ according to the intended context.There are changes and differences to adjust the characteristics of each locality. Discussion living tradition canbe seen in three forms, namely written, oral, and practical. All three models and forms of the living traditionof inter-related with each other